Lamellar orientation control of Ti–47Al–0.5W–0.5Si by directional solidification using β seeding technique. (June 2016) - Liu, Tong; Luo, Liangshun; Su, Yanqing; Guo, Jingjie; Fu, Hengzhi
Abstract: In this paper, we report a β seeding technique for the lamellar orientation controlling in TiAl alloy, which is a novelty and effective method for aligning the lamellar orientation of Ti–47Al–0.5W–0.5Si with primary α phase. The shorter composition transition zone and simpler process procedure can improve the deficiency of α seeding technique. The proper temperature gradient and normal growth rate are necessary for aligning the lamellar orientation in TiAl alloy with primary α phase using β seeding technique. Graphical abstract: